MY CART (5)

Use Coupon: CART20 and get 20% off on all online Study Material

ITEM

DETAILS

MRP

DISCOUNT

FINAL PRICE

Total Price: Rs.

There are no items in this cart.

Continue Shopping

Continue Shopping

Menu

` tell me the fourth equation of motion and meaning of each symbol occurring in it...if possible also tell the consequent equations of motion...`

6 years ago

Dear Indrayani

- v= u + at
- s =( u + v ) t /2
- s = ut + at
^{2}/2- v
^{2}= u^{2}+ 2as

The following are thevariablesused in these equations:

- t is the length of the interval of time and measured in seconds.
- u is the initial speed of the object or the speed at the beginning of the time interval, measured in ms
^{-1}.- v is the final speed of the object or the speed at the end of the time interval, measured in ms
^{-1}.- a is the acceleration of the object within the time interval t measured in ms
^{-2}.- s is the distance covered or the displacement of the object during the time interval t, measured in metres.
Derivation of Newton's Equations of Motion:

Derivation of First and second equations of motion:

We know that,Velocity is the Change in displacement / Change in time,

v = ds/dt = s/t andAcceleration is the change in velocity / change in time,

a = dv/dt = (v-u)/t

Or the acceleration is the change in speed per unit time, so:

a = (v-u) /t

or at = v-u

or v= u + at and it is thefirst Equation of Motion.

We also know that the average speed during the time interval t is equal to displacement per unit time, so:

(u + v)/2 = s / t since Average speed = (u+v)/2

s / t = (u + v)/2

ors = ( u + v ) t /2and this is thesecond equation of motion.

Derivation of third and Fourth Equations of Motion:Derivation of third equation of motion

The third equation of motion can be derived by substituting the value of v from the first equation into the second equation.

First equation isv= u +at

And the second equation is s = (u+v)t /2

Or s=[u + (u+at)] t /2 =[2u+at]t /2 = [2ut+ at2] / 2 =ut + at2/2

Or s=ut + at2/2 and this is thethird equation of motion.

Derivation of fourth equation of motion

To derive the fourth equation of motion, first we have to consider the equation for acceleration and then to rearrange it.

Accelerationa = (v-u) /t

Or at = (v-u)

Ort = (v-u) /a

Next step is to substitute the equation for the time t into the second equation of motion s=ut + at2/2 to obtain:

s = u[(v-u)/a] + a [(v-u)/a]^{2}/2

or s = u(v-u)/a + (v-u)^{2}/2a

or s =[2u+v-u](v-u)/2a

or s = (u+v)(v-u)/2a = (v+u)(v-u)/2a

ors= (v^{2}-u^{2})/2a

or2as = v^{2}–u^{2}^{}

orv^{2}–u^{2}= 2as

or v^{2}= u^{2}+ 2as and thisequation of motioncan be used to find the final velocity or the distance travelled if the other values are given.All the best.AKASH GOYALAskiitiansExpert-IIT Delhi

Please feel free to post as many doubts on our discussion forum as you can. We are all IITians and here to help you in your IIT JEE preparation.

Win exciting gifts by answering the questions on Discussion Forum. So help discuss any query on askiitians forum and become an Elite Expert League askiitian.

Now you score 5+15 POINTS by uploading your Pic and Downloading the Askiitians Toolbar respectively: Click here to download the toolbar.

6 years ago

S=(u+v)t/2Derivation-We know that a=(v-u)/t and s=ut+(at^2)/2S=ut+((v-u)/t)t^2S=ut+(v-u)t/2Take t as commonS=t[2u+v-u]/2S=t(v+u)/2 Proved

8 months ago

Think You Can Provide A **Better Answer ?**

Answer & Earn Cool Goodies

Have any Question? Ask Experts

Post Question

copyright © 2006-2017 askIITians.com

info@askiitians.com